The Influence of Counseling on Increasing the Knowledge of Cikelet Village Community Regarding Halal Products - Fauziah, Nenden; Lubis, Novriyanti; Handayani, Niknik; Lindayani, Lindayani; Sution, Sution; Rosalia, Novita; Widia, Putri; Nugraha, Robi Asran; Aladawi, Syifa; Taufikurohman, Ikbal (Indonesian Journal of Community Empowerment (IJCE), 2022)
The problem found in Cikelet village, Garut district, was the sensitive issue regarding the halalness of a product. Most village residents do not yet know the authorized institution that provides a halal certificate to a product, the characteristics of a halal product in terms of its packaging and the basic laws of halal products. With the KKN program through community service activities, the PKM team from the Garut University Pharmacy in the KKN program provided a solution to this problem through the promotion of halal food and drinks by providing brochures and direct counseling to residents of various age levels and professions. pre and post test to evaluate the success of the socialization. The aim and targeted outcomes of this outreach are to see an increase in Cikelet residents' knowledge of halal products so that they can increase awareness in choosing something that is safe, good for health and halal. Permasalahan yang ditemukan di desa Cikelet kabupaten Garut adalah adanya isu sensitif mengenai kehalalan suatu produk. Sebagian besar warga desa belum mengetahui lembaga yang berwenang yang memberikan sertifikat halal pada suatu produk, ciri produk halal ditinjau dari kemasannya dan hukum dasar dari produk halal. Dengan adanya program KKN melalui kegiatan pengabdian kepada masyarakat tim PKM dari Farmasi Universitas Garut pada program KKN memberikan solusi terhadap permasalah tersebut melalui sosialisasi makanan dan minuman halal melalui pemberian brosur dan penyuluhan langsung kepada warga dengan berbagai tingkatan usia dan profesi, selain itu juga dilakukan pre dan post test untuk mengevaluasi keberhasilan dari sosialisasi tersebut. Tujuan dan luaran luaran yang ditargetkan dari penyuluhan ini untuk melihat peningkatan pengetahuan warga Cikelet terhadap produk halal sehingga dapat meningkatkan kesadaran dalam memilih suatu suatu yang aman, baik untuk kesehatan dan halal.